Anodic MAO coating formation on Ti-25Ta alloy - Kuroda, Pedro Akira Bazaglia; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (Elsevier, 2024)
This study aims to produce an anodic layer using the micro-arc oxidation (MAO) technique on the Ti-25Ta alloy by changing the threshold current value in surface treatment processes (1.0, 1.5, 2.0, and 2.5 A). The MAO treatment processes were carried out by applying a voltage of 300 V for 60 s, and the maximum current value was changed. The results showed that increasing the current limit value resulted in an increase in the amount of rutile phase in the films, as well as an increase in the coating's thickness and contact angle. Furthermore, all coatings showed good adhesion with the Ti-25Ta substrate.
Keywords: Micro-arc oxidation; Surface characterization; Ti-25Ta alloy